Not by War Alone - Jabber, Paul (Berkeley, CA : : University of California Press, 2020)
The Middle East remains the most politically volatile and militarily unstable region in the world. It is also in relative terms the most heavily armed; and the influx of American, Soviet, French and other weaponry continues unabated. Moreover, the Arab-Israeli conflict invites competition in nuclear armaments. Accordingly a concern of public policy must be the promotion of strategic stability between potential adversaries and the imposition of effective restraints on the several interrelated arms races in the region. In the absence of negotiated solutions to existing disputes, or as a feature of future peace accords, arms-control measures could be of crucial importance in preventing the outbreak of war. Jabber explores the prospects for arms control in the specific contexts of the Arab-Israeli dispute and of military developments since the war of October 1973. Seeing lessons from history, and drawing on previously untapped materials, he includes a case-study of an actual Middle East arms-control system that was instituted by the United States, Great Britain, and France under the Tripartite Declaration of May 1950. Designed to prevent further warfare after the establishment of Israel by maintaining a stable balance of power through the rationing of arms supplies, this agreement was soon circumvented by its French sponsors, and it collapsed altogether following the emergence in 1955 of the Soviet Bloc as a major source of arms. After analyzing the Tripartite system--a unique experiment in coordinated, long-term, multilateral arms control on a regional level--Mr. Jabber defines the basic requirements for effective and curable international accords of this kind by exploring the relationships among the international arms trade, the purposes of arms control, and the political objectives and security interests of both suppliers and recipients of.
Arms. This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1981.
Frontmatter -- CONTENTS -- TABLES -- PREFACE -- PART I. THE PROBLEM AND ITS SETTING -- CHAPTER 1. INTRODUCTION -- CHAPTER 2. PROBLEMS AND PROSPECTS FOR ARMS CONTROL IN THE ARAB-ISRAELI CONFLICT -- CHAPTER 3. MULTILATERAL APPROACHES TO ARMS-TRANSFER LIMITATION -- PART II. LESSONS OF THE PAST: THE 1950-1955 ARMS RATIONING REGIME -- CHAPTER 4. SUPPLY AND CONTROL: ARMS AND THE TRIPARTITE DECLARATION OF MAY 1950 -- CHAPTER 5. OPERATIONAL ASPECTS OF THE ARMS CONTROL SYSTEM -- CHAPTER 6. ARMS FOR EGYPT: THE LITMUS TEST -- PART III. CONCLUSIONS -- CHAPTER 7. THE USE AND MISUSE OF ARMS CONTROL -- SELECTED BIBLIOGRAPHY -- INDEX
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 18. Sep 2023).
JSTOR
Keywords: Middle East -- Politics and government -- 1945-; Middle East -- Defenses; Arms control -- Middle East; Arms control; Middle East -- Politics and government; conflict studies; defence policy; interdisciplinary studies; international relations; military affairs; peace and conflict studies; political science; war .; Moyen-Orient -- Politique et gouvernement -- 1945-; Armements -- Contrôle.; Moyen-Orient -- Politique et gouvernement; NON-CLASSIFIABLE.; Arms control; Military readiness; Politics and government; Middle East; Since 1945